Invasive Pulmonary Aspergillosis - Ledoux, Marie-Pierre; Guffroy, Blandine; Nivoix, Yasmine; Simand, Célestine; Herbrecht, Raoul (Seminars in Respiratory and Critical Care Medicine, 2020)
Invasive pulmonary aspergillosis (IPA) remains difficult to diagnose and to treat. Most common risk factors are prolonged neutropenia, hematopoietic stem cell or solid organ transplantation, inherited or acquired immunodeficiency, administration of steroids or other immunosuppressive agents including monoclonal antibodies and new small molecules used for cancer therapy. Critically ill patients are also at high risk of IPA. Clinical signs are unspecific. Early computed tomography (CT)-scan identifies the two main aspects, angioinvasive and airway invasive aspergillosis. Although CT-scan findings are not fully specific they usually allow early initiation of therapy before mycological confirmation of the diagnosis. Role of 18F-fludeoxyglucose positron emission tomography with computed tomography (18F-FDG PET/CT) is discussed. Confirmation is based on microscopy and culture of respiratory samples, histopathology in case of biopsy, and importantly by detection of Aspergillus galactomannan using an immunoassay in serum and bronchoalveolar lavage fluid. Deoxyribonucleic acid detection by polymerase chain reaction is now standardized and increases the diagnosis yield. Two point of care tests detecting an Aspergillus glycoprotein using a lateral flow assay are also available. Mycological results allow classification into proven (irrespective of underlying condition), probable or possible (for cancer and severely immunosuppressed patients) or putative (for critically ill patients) IPA. New antifungal agents have been developed over the last 2 decades: new azoles (voriconazole, posaconazole, isavuconazole), lipid formulations of amphotericin B (liposomal amphotericin B, amphotericin B lipid complex), echinocandins (caspofungin, micafungin, anidulafungin). Results of main trials assessing these agents in monotherapy or in combination are presented as well as the recommendations for their use according to international guidelines. New agents are under development.
Keywords: Aspergillus fumigatus; tracheobronchial aspergillosis; voriconazole; Isavuconazole; posaconazole; combination therapy; review; galactomannan; acute myeloblastic leukemia; allogeneic hematopoietic stem cell transplantation; solid organ transplantation